2015
DOI: 10.1007/s00709-015-0847-9
|View full text |Cite
|
Sign up to set email alerts
|

A cold-tolerant evergreen interspecific hybrid of Ocimum kilimandscharicum and Ocimum basilicum: analyzing trichomes and molecular variations

Abstract: Ocimum (Lamiaceae) is an important source of essential oils and aroma chemicals especially eugenol, methyl eugenol, linalool, methyl chavicol etc. An elite evergreen hybrid has been developed from Ocimum kilimandscharicum and Ocimum basilicum, which demonstrated adaptive behavior towards cold stress. A comparative molecular analysis has been done through RAPD, AFLP, and ISSR among O. basilicum and O. kilimandscharicum and their evergreen cold-tolerant hybrid. The RAPD and AFLP analyses demonstrated similar res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…ISSR markers also have the ability to amplify DNA fragments that are present at an amplifiable distance between two identical microsatellite repeat regions orientated in opposite direction (Reddy et al 2002). High polymorphism of ISSR was also reported in many previous studies, as in the case of Mentha arvensis, Ocimum (Malav et al 2015;Dhawan et al, 2016;Chaturvedi et al 2018;Alves et al 2019;Gupta et al 2021). Previous studies have also recommended that SCoT markers work better performance than other molecular marker systems in other plants (Luo et al, 2011).…”
Section: Speciessupporting
confidence: 71%
“…ISSR markers also have the ability to amplify DNA fragments that are present at an amplifiable distance between two identical microsatellite repeat regions orientated in opposite direction (Reddy et al 2002). High polymorphism of ISSR was also reported in many previous studies, as in the case of Mentha arvensis, Ocimum (Malav et al 2015;Dhawan et al, 2016;Chaturvedi et al 2018;Alves et al 2019;Gupta et al 2021). Previous studies have also recommended that SCoT markers work better performance than other molecular marker systems in other plants (Luo et al, 2011).…”
Section: Speciessupporting
confidence: 71%
“…× intermedia but higher expression than pure J. regia as well. Some cold hardy gene expression studies reported that F1 hybrids of Ocimum kilimandscharicum (Camphor Basil) showed higher expression levels than pure species (Dhawan et al, 2016). Interspecific hybrid Pinus spp.…”
Section: Gene Expression Through Qpcrmentioning
confidence: 99%
“…O. basilicum was found to ameliorate CUMS-induced neuronal changes in MOB especially mitral cells. This effect might be attributed to the bioactive compounds present in O. basilicum essential oils like linalool, eugenol, cineole, and many other compounds that exert free radical scavenging activity (8,24). These essential oils inhibit liposomal peroxidation and scavenge hydroxyl radicals, NO, and superoxide anion.…”
Section: Discussionmentioning
confidence: 99%
“…Ocimum basilicum (O. basilicum), also called basil or Raihan, is an annual plant used as a spice for culinary purposes in salads and pasta sauces. It is extensively utilized as a flavoring agent and in production of perfumes and soap (8,9). In addition, it is used for medicinal purposes due to its antidepressant, anxiolytic, sedative activities (10,11).…”
Section: Introductionmentioning
confidence: 99%